Wave- and current-dominated combined orthogonal flows over fixed rough beds. (1st May 2021) - Faraci, Carla; Musumeci, Rosaria Ester; Marino, Massimiliano; Ruggeri, Alessia; Carlo, Lilia; Jensen, Bjarne; Foti, Enrico; Barbaro, Giuseppe; Elsaßer, Bjorn
Abstract: Orthogonal wave-current interaction often occurs in coastal regions, when waves approach the shoreline near-orthogonally and longshore currents are present. Notwithstanding its wide relevance, this phenomenon is far from being understood to a full extent, especially in the presence of bed roughness. Indeed the effects on the apparent roughness due to the combination of steady currents and surface waves propagating at right angles are still a matter of debate, both in the current and in the wave dominated cases. To this aim, the hydrodynamic effects of an orthogonal regular wave on a current propagating over a rough bed were investigated; two different rough beds, one sandy and one made of gravel, were considered. Both surface elevation and velocity profiles were acquired by means of an array of wave gauges and Micro Acoustic Doppler Velocimeters positioned within the tank. Here the range of the investigated parameters was significantly enlarged with respect to the existing literature studies. The present paper focuses on the analysis of the mean velocity profiles. More specifically, observation of velocity profiles shows that the current to wave velocity ratio and the bed roughness play an important role, by impacting the value of the apparent roughness. Indeed it was found that as far as the flow is current dominated the addition of waves on the current increases the flow resistance. The opposite happens when the flow is wave dominated, irrespective of the bed roughness type. In particular, the apparent roughness increases as far as the wave plus current to current only friction velocity ratio increases. The increase is more rapid if the wave plus current prevails on the current only friction velocity. Highlights: Wave-current interaction over rough beds in wave-dominated and current-dominated conditions. Gravel bed generated-turbulence induces smaller gradients in the near bed velocities than sandy bed. The nature of the rough bed does not influence the non dimensional apparent roughness, that increases with friction velocity. The possibility to determine either the apparent roughness or the friction velocity from the other one is provided.